Effect of lateral oblique cyclic loading on microleakage and screw loosening of implants with different connections - Hakimeh Siadat; Hossain Najafi; Marzieh Alikhasi; Babak Falahi; Elaheh Beyabanaki; Farid Zayeri (Tabriz University of Medical Sciences, 2018)
Background. The implant connection type might affect microleakage and screw loosening in two-piece implants. The aim of this study was to measure microleakage and screw loosening of two connections of Noble Biocare implant system before and after cyclic loading. Methods. Twelve samples were categorized into two groups: external hexagon (Branemark) and internal hexagon connection (Noble Active) and two implants as controls. The abutments were tightened to a 35 Ncm torque. Initial torque loss (ITL) was measured five minutes after retightening the abutment, using a digital torque wrench. The samples were covered with putty material to the abutment‒implant junction. Customized metal crowns with 45° inclinations were placed on the abutments and cyclic loading was performed accordingly. Thereafter, the secondary torque loss (STL) was measured. Microleakage test was also performed. Data were analyzed with Mann-Whitney and Wilcoxon tests (α=0.05). Results. There were no statistically significant differences between the two phases of gamma counting between and within two groups (P>0.05). However, STL after cyclic loading was less than ITL in both groups (P=0.042). Conclusion. Connection type and cyclic loading had no significant effect on microleakage. Furthermore, the internal connection had less TL as compared to the external connection. In addition, the STLs were less than ITLs in both groups.